"Linking as one" : an intimate breastfeeding moment : a thesis presented in fulfillment of the requirements for the degree of Doctor of Philosophy in Nursing at Massey University, Palmerston North, New Zealand - Dignam, Denise Miriam (Massey University, 2001)
Breastfeeding is more than the act of providing nutrition to an infant. It is a dynamic interpersonal process, frequently suggested by both women and authors to be an intimate activity. Health professionals have tended to explore the biophysical aspects of breastfeeding largely ignoring the breastfeeding woman's perspective and the effect social and psychological processes have on breastfeeding success. This grounded theory study drew on a range of data sources to describe breastfeeding womens' experience of intimacy. Data included interviews with twenty women participants, observational field notes, theoretical memos, drawings, literature and pictorial work. The study supported the premise that women experienced moments of intimacy when breastfeeding. Breastfeeding is represented in the basic social psychological process 'linking as one'. Linking as one is the intimate act of gifting, for comfort, pleasure and growth, human milk and human contact to a baby or child. 'Linking as one' is mutually exclusive and mutually satisfying to both participants. It is not all women's experience nor is it associated with every breastfeeding encounter. The findings support a substantive descriptive model of the breastfeeding process that represents and facilitates intimate breastfeeding moments. The model provides a framework for theoretical research, which may lead to further conceptual refinement. The model also provides a framework for education curricula and nursing clinical practice. Clinical application includes the use of concepts as prompts from which to explore interpersonal breastfeeding dynamics with breastfeeding clients. The concepts include breastfeeding comfort, ownership of the breast, mutual gifting and knowing. Exploration of these concepts may enable breastfeeding women to maintain and promote successful breastfeeding experiences.
Content removed due to copyright restriction Dignam, D. M. (1995). Understanding intimacy as experienced by breastfeeding women. Health Care for Women International, 16(5), 477-485
Keywords: Mother-baby relationship; Breastfeeding experiences; Fields of Research::320000 Medical and Health Sciences::321100 Nursing